Selection of Unit Design for Teluk Buyung 4 Water Treatment Plant (WTP), Bekasi City, West Java, Indonesia - Sharmaina Fadhilah Nasution; Riana Ayu Kusumadewi; Widyo Astono (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2022)
The city of Bekasi is experiencing rapid development so the demand for water is increasing. To increase service coverage and meet the drinking water needs of the people of Bekasi City with a quality that meets the Minister of Health Regulation No. 492 of 2010, it is planned to up rate the capacity that the Teluk Buyung 4 WTP has a capacity of 300 L/second with a raw water source, namely the West Tarum Secondary Channel. The Teluk Buyung 4 WTP is planned to use the design criteria from the Equivalent WTP evaluation, namely Teluk Buyung 3 WTP and literature studies. Teluk Buyung 4 WTP uses processing units, intake unit, hydraulic coagulation, hydraulic flocculation, plate settler sedimentation, rapid sand filtration, disinfection, and reservoir. The data used in the planning process is divided into two, namely primary data and secondary data. The intake unit has several components, namely a barscreen, sluice gate, carrier channel, and collecting well. The pre-sedimentation unit consists of 2 tanks and is channeled to a collection well and then pumped to the WTP. The coagulation unit uses hydraulic coagulation with a plunge of 1 tub. The coagulant used was PAC at a dose of 25 mg/L. The flocculation unit uses hydraulic flocculation with up and down flow with 2 tubs. The sedimentation unit uses a plate settler with 2 tanks. The filtration unit uses a rapid sand filter with dual media, namely anthracite media and sand media and has 7 tubs. Disinfection process uses NaOCl with a dose of 41.67 mg/L. The reservoir unit uses 1 tub with a ground reservoir type.